2020
DOI: 10.1097/md.0000000000019871
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel analysis of hemodialysis-associated infection among end-stage renal disease patients: results of a retrospective cohort study utilizing the insurance claim data of Fukuoka Prefecture, Japan

Abstract: The presence of comorbid conditions along with heterogeneity in terms of healthcare practices and service delivery could have a significant impact on the patient's outcomes. With a strong interest in social epidemiology to examine the impact of health services and variations on health outcomes, the current study was conducted to analyse the incidence of hemodialysis-associated infection (HAI) as well as its associated factors, and to quantify the extent to which the contextual effects of the care facility and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Nevertheless, the analyses of claims data provide better population-based estimates and thus wider population coverage. Past studies using a similar database reported a high penetration rate (98.6%) of insurance claims data in Fukuoka prefecture [52][53][54]. Primary diagnosis, used as a 'surrogate' for disease-specific mortality, might not represent the actual causes of death among hemodialysis patients.…”
Section: Plos Onementioning
confidence: 99%
“…Nevertheless, the analyses of claims data provide better population-based estimates and thus wider population coverage. Past studies using a similar database reported a high penetration rate (98.6%) of insurance claims data in Fukuoka prefecture [52][53][54]. Primary diagnosis, used as a 'surrogate' for disease-specific mortality, might not represent the actual causes of death among hemodialysis patients.…”
Section: Plos Onementioning
confidence: 99%
“…This instrument was widely used in Japan. 14,15 The use of this instrument in the previous study showed that the index has acceptable reliability, thus could be applied to studies analyzing healthcare data from the Japanese insurance claims database. 16 The International Classification of Diseases 10th Revision (ICD-10) coded data were used to capture patients' morbidity status.…”
Section: Data Sourcementioning
confidence: 99%